Understanding the impacts of climate change on cultural heritage buildings: a case of York, UK - Ksenia Chmutina; Rohit Jigyasu; Lee Bosher (2016)
Cultural heritage is not only an important part of a country’s identity but also a key driver of tourism (which can play an important role in a nation’s economic and social resilience). However worldwide heritage buildings are gradually becoming more vulnerable, due to natural decay and deterioration, effects of climate change, and human-induced impacts, such as poor or ineffective maintenance. An increased number of extreme weather events, many of which are associated with the impacts of climate change, are posing significant problems in managing and conserving cultural heritage around the globe. Being exposed to a number of natural hazards and having a great cultural heritage, York (UK) presents a case study that provides the basis for the exploration of the strategies required for the improved disaster risk management of vulnerable heritage buildings. Through the engagement with practitioners responsible for the management of a range of heritage sites, this paper identifies the challenges faced when considering climate change adaptation measures. It argues that improved climate change adaptation and enhanced hazard mitigation strategies, involving a broad range of suitably trained stakeholders, are extremely important considerations when it comes to the assessment, maintenance and conservation of cultural heritage.